How the economic and financial situation of the community affects sport clubs' resources: Evidence from multi-level models - Pamela Wicker; Christoph Breuer (International Journal of Financial Studies, 2015)
In many Western countries, local community sport clubs are important providers of leisure, sport, and social programs. These sport clubs are nonprofit organizations, which operate in an increasingly challenging environment. This study considers a club's direct local environment, i.e., the community the club is located in. The open systems model and the resource dependence represent the theoretical framework. The purpose of this research is to examine the effect of the financial and economic environment in the community on the resource situation of sport clubs (human, infrastructure, and financial resources). The empirical evaluation is undertaken using data from a nationwide survey of non-profit sport clubs in Germany (organizational level; n = 19,345), which are combined with secondary data on community characteristics (community level; n = 3153). Given the hierarchical data structure, multi-level analyses are applied. The results show that volunteer problems are smaller among clubs in communities with high unemployment. Facility and financial problems are greater in large communities. Sport clubs located in communities that could break even were also more likely to break even themselves. The findings show that resource problems are not necessarily due to poor club management, since higher-level (community) factors significantly affect the resource situation of sport clubs too.
Keywords: 330; environment; community; finance; nonprofit sport club; multi-level analysis; resources